THE EFFECT OF GREEN ACCOUNTING, CARBON EMISSION, ECO- EFFICIENCY, AND GENDER DIVERSITY ON FIRM VALUE - Firdaus; Dian Saputra; Yovan Allif Ananda (International Conference On Law And Social Sciences, 2024)
This study aims to explore the complex relationship between Green Accounting, Carbon Emission, Eco- efficiency, and Gender Diversity on firm value in the raw material sector. The research sample consists of 50 companies in the raw materials sector on the Indonesia Stock Exchange. Data were obtained from financial statements, annual reports, and corporate sustainability reports. The analysis was conducted using multiple regression with the SMARTPLS 3 tool. The results showed a substantial relationship between Carbon Emission, Eco-efficiency, Gender Diversity and firm value in the raw goods sector. This study uses cross-sectional, this study limits the ability to see the development of the relationship between variables in the long term. Longitudinal studies or long-term trend analysis may be required to provide deeper understanding. The findings provide new insights into the complex relationship between environmental, social and firm value factors. Companies in the raw goods sector can utilize Carbon Emission, Eco-efficient and Gender Diversity practices to increase their long-term value. This research contributes to the understanding of the intricate connection between environmental, social and firm value factors, and offers new perspectives for business practitioners and academics.